Analisis Sistem Tataniaga Cabai Merah di Desa Besakih, Kecamatan Rendang, Kabupaten Karangasem - ADNYASARI, PUTU SRI; DEWI, RATNA KOMALA; SUSRUSA, KETUT BUDI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.4, Oktober 2017DO - 10.24843/JAA.2017.v06.i04.p03, 2017)
Analysis of Red Chili Trading System in Besakih Village, Rendang Sub-District of Karangasem Regency Besakih village as one of the centers of red chilli production in Karangasem Regency has several marketing channels with different prices between producers and consumers. This study aims to investigate the channels of trading, commercial institutions, and the red chili trading system in the Village of Besakih. The data used were quantitative and qualitative data. The analysis used descriptive qualitative. Respondents in the study were 38 farmers determined by proportional random sampling method and 23 respondents of trading institutions determined by snowball sampling method. The research result was six channels of trading system, (1) Farmers – Local Assembly Trader’s - Retailers - Consumers; (2) Farmers - Local Assembly Trader’s - Retailers - Consumers; (3) Farmers – Sub Terminal of Agribusiness - Retailers - Consumers; (4) Farmers - Sub Terminal of Agribusiness - Retailers - Consumers; (5) Farmers - Sub Terminal of Agribusiness - Consumers; (6) Farmers - Sub Terminal of Agribusiness – Market in Lombok. The most efficient trading channel was channel II. The trading agency consists of local assembly trader’s / inter-city / inter-district traders, Sub Terminal of Agribusiness / inter-city / inter-district / inter island traders, traditional market retailers and supermarket retailers. Each of the trading system institution involved the three main functions of exchange, physical function and facility function. However, the activities undertaken by each institution were different.